2016
DOI: 10.1016/j.apjtm.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Kalopanax septemlobus leaf inhibits HepG2 human hepatocellular carcinoma cell proliferation via inducing cell cycle arrest at G 1 phase

Abstract: Overall, our findings suggest that EEKS may be an effective treatment for liver cancer through suppression of cancer cell proliferation via G1 cell cycle arrest. Further studies are required to identify the active compounds in EEKS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Chinese medicinal herbs have been used for the treatment of various diseases in China and Southeast Asia (23). Also, many studies have focused on the anticancer effects of phytochemicals which is contained in natural plant (3,(7)(8)(9)(10). In the present study, we examined whether ethanol extracts from C. monnieri (CME)-induced apoptotic and cell cycle arrest effects were occurred by p53-dependent or p53-independent mechanism in HepG2 (wild-type p53) and Hep3B (p53-null) hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinese medicinal herbs have been used for the treatment of various diseases in China and Southeast Asia (23). Also, many studies have focused on the anticancer effects of phytochemicals which is contained in natural plant (3,(7)(8)(9)(10). In the present study, we examined whether ethanol extracts from C. monnieri (CME)-induced apoptotic and cell cycle arrest effects were occurred by p53-dependent or p53-independent mechanism in HepG2 (wild-type p53) and Hep3B (p53-null) hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that bioactive compounds from natural plant extracts play a crucial role as potential therapeutic agents (6). Many plant extracts induce anticancer effects such as anti-proliferative and anti-metastatic effects and cell cycle arrest in various cancer cell lines (7)(8)(9). Moreover, the anticancer activity of natural plant extracts has been investigated in HepG2 and Hep3B hepatocellular carcinoma cells (3,10).…”
Section: Introductionmentioning
confidence: 99%
“…are sold at local markets in Korea ( Table 1 ). The extracts and compounds obtained from traditional GLVs (1–18) have been shown to possess antioxidant [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], anticancer [ 18 , 23 , 24 , 25 , 26 ], antiinflammation [ 20 , 25 , 27 , 28 ], anti-melanogenic [ 29 , 30 ], anti-fatigue [ 31 ], anti-obesity [ 32 , 33 ], antidiabetic [ 34 ], and immunostimulatory [ 35 ] activities. GLVs have abundant phytopigments.…”
Section: Introductionmentioning
confidence: 99%